The Application of Simple Multiparty Concept to Maintain Political Stability in Carrying Presidential Candidates in the 2024 Election (Activa Yuris: Jurnal Hukum, 2022)
The 2019 election imposes a fairly high threshold for political parties to be able to nominate presidential candidates. PDIP as the party with the largest vote does not want to reduce the 20 percent threshold as a form of commitment to maintain political stability so that there is no political commotion and minimize the presence of incompetent candidates. This figure makes other parties to form a coalition that is divided into two presidential candidates. Although it appears that there is a multi-party simplification in accordance with the presidential system, the determination of the threshold is not in accordance with Article 6A paragraph (3) of the third Amendment of the 1945 Constitution. The purpose of this study is to review the application of a simple multiparty concept in maintaining political stability and to review the challenges of implementing a simple multiparty in carrying presidential candidates to meet the 2024 election. The method used in this study is a legal approach and a case approach with data collection through literature studies. The results of this study indicate that the implementation of a simple multiparty in the upcoming 2024 election is pursued by a presidential threshold of 0 percent, so that each political party can nominate a presidential candidate either alone or in a coalition, meaning that there is no simple multiparty. On the other hand, if the presidential threshold is set to 0 percent, the consolidation of democracy and political stability will be very noisy and require expensive costs for the implementation of the 2024 election contestation